Chronic mechanical trauma/irritation and oral carcinoma: A systematic review showing low evidence to support an association. (20th October 2021) - Pentenero, Monica; Azzi, Lorenzo; Lodi, Giovanni; Manfredi, Maddalena; Varoni, Elena
Abstract: Background: Chronic trauma of oral mucosa, resulting from repeated and persistent mechanical irritative action of an intraoral injury agent, has repeatedly been reported to be possibly implicated in the development of oral squamous cell carcinoma (OSCC). Objectives: The present systematic review aimed to assess whether chronic mechanical trauma can be considered a risk factor for OSCC. Data sources: PubMed, CENTRAL (Cochrane Central Register of Controlled Trials), Scopus; EMBASE, Web of Science. Study eligibility criteria: Cohort studies comparing OSCC incidence among subjects with/without chronic mechanical trauma or case–control or cross‐sectional studies comparing chronic mechanical trauma among subjects with/without OSCC. Results: Only one prospective case–control study fulfilled the inclusion criteria, but the quality of the evidence provided is not enough to define trauma as a risk factor for OSCC. The main limitation is the presence of only one case–control study at high risk of bias. In the absence of strong evidence supporting the role of trauma in OSCC, a thorough discussion on trauma and carcinogenesis has been performed. Conclusions: Available evidence does not support an active role for chronic trauma in oral carcinogenesis, neither as promoter nor as progressor factor. Prospective cohort studies able to better assess trauma in OSCC are needed.